El Departamento Nacional del Trabajo y la conciliación del conflicto capital-trabajo. Mediaciones entre la Sociedad Tipográfica Bonaerense y los sectores patronales (1906-1907) - Sebastián Alejo Fernández (Perspectivas Metodológicas​)
In Argentina at the beginning of the 20th century, the working conditions, sanitation, and the salary of the urban working mass were gravely precarious. Faced with the formation of trade union organizations and the use of the strike as a method of protest in pursuit of the conquest of rights, the government promoted the creation of the National Department of Labor, this institution being in charge of carrying out a survey of the Argentine labor situation, to suggest draft labor laws to provide a regulatory legal framework and mainly to act as arbitrator of conflicts between the labor and employer sectors. The capacity of the National Labor Department to act was seriously limited by the lack of an organic law that would regulate it and be legitimate, but this did not mean that it was recognized as a mediator. This work will use case studies to analyze the actions of the National Department of Labor in the face of the struggles between the Buenos Aires Typographic Society and the UIA between 1906 and 1907 in order to observe what was the influence of said state institution and what recognition achieved at the time of conflict resolution.